Characterization and Removal of Condensable Particulate Matter in Flue Gas Studied with Cold Electrode Electrostatic Precipitator - Wenting Liu; Bowen Zhao; Xin Wang; Jianyi Lu (Aerosol and Air Quality Research)
Abstract The emissions of filterable particulate matter (FPM) from stationary source flue gases are well-controlled, but condensable particulate matter (CPM) is becoming a growing concern as it’s more challenging to eliminate and poses a more significant environmental threat. Conventional air pollution control devices (APCDs) in coal-fired power plants have limited control over CPM. To address the issue, our research employed the Impact Condensation Method based on EPA Method 202 to test the emissions of CPM and FPM at the stack inlet in a coal-fired power plant. Additionally, a cold electrode electrostatic precipitator (CE-ESP) was installed to remove CPM. According to the study, CPM was emitted at the stack inlet with an average concentration of 30.2 mg Nm−3, which far exceeds the concentration of FPM (3.7 mg Nm−3) and the Chinese ultra-low emission (ULE) standard for particulate matter. Regarding emission characteristics, the most significant proportion of total detected anionic water-soluble was SO42− in CPM. Na and Ca were the most abundant elemental metal components, followed by Pb. The primary organic compounds found in CPM were hydrocarbons, olefins, and esters. This was further evidence of the environmental and human hazards of CPM. The removal of CPM is highly efficient with multi-field synergistic CE-ESP that combines temperature, electric, and concentration fields. The removal rate can reach up to 93%. The average CPM concentration after removal was 2.8 mg Nm−3, and the CE-ESP had a significant removal effect on SO42−, Ca, As, esters, and olefins from CPM. Moreover, the CE-ESP showed higher efficiency for the inorganic substance than the organic substance. The CPM concentration in the treated flue gas was significantly reduced and could meet the ULE standard before emission. This study indicated that the concentration of CPM was extremely high at the stack inlet. However, CE-ESP was able to remove CPM efficiently.